Calculus 8th Edition

Published by Cengage
ISBN 10: 1285740629
ISBN 13: 978-1-28574-062-1

Chapter 17 - Second-Order Differential Equations - 17.2 Nonhomogeneous Linear Equations - 17.2 Exercises - Page 1208: 25


$y= [c_1+\ln (1+e^{-x} )] e^x +[c_2-e^{-x} +\ln (1+e^{-x} )] e^{2x}$

Work Step by Step

We are given that $y''-3y'+2y=\dfrac{1}{1+e^{-x}}$ The particular solution: $y_p=u_1 e^x+u_2 e^{2x}$ $u'_1=\dfrac{-[e^{-x}]}{1+e^{-x}} $ and $u_1=\int \dfrac{-[e^{-x}]}{1+e^{-x}}=\ln (1+e^{-x})$ and $u'_2=\dfrac{e^{x}}{e^{3x}+e^{2x}}$ and $u_2=\int \dfrac{e^{x}}{e^{3x}+e^{2x}}$ or, $=\ln (\dfrac{e^x+1}{e^x}) -e^{-x}$ or, $=\ln (1+e^{-x})-e^{x} $ We have $y_p=(e^x) \ln (1+e^{-x}) +(e^{2x}) [\ln (1+e^{-x})-e^{x}] $ Hence, $y= [c_1+\ln (1+e^{-x} )] e^x +[c_2-e^{-x} +\ln (1+e^{-x} )] e^{2x}$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.